The Influence of Peer Groups, Social Media Advertisements, Preventive Policies of the School of Origin and Personal Religiosity on the Level of Exposure to Online Gambling in New Students of Muhammadiyah Universities in Greater Jakarta - Wijaya Saputra, Dendi; Husainah, Nazifah; Iswan (Yayasan Mentari Madani, 2025)
This research is motivated by the limited studies on online gambling exposure among high school graduates entering college, despite its significant impact on adolescent behavior and mental health in Indonesia. The study aims to measure exposure levels and examine the effects of two risk factorsgambling advertising on social media and peer association and two protective factors preventive school policies and personal religiosity among new students at Muhammadiyah Universities (PTM) in Greater Jakarta. Using a quantitative approach, the study involved 584 first-year students selected through simple random sampling from four PTMs: UMJ, UHAMKA, UMT, and UMBARA. Data were collected via an online questionnaire employing the Problem Gambling Severity Index (PGSI) and researcher-developed Likert scales, then analyzed using binary logistic regression. Results revealed that 18.8% of respondents had varying levels of exposure to online gambling. Logistic regression showed significant influences: gambling advertising (OR = 9.14) and peer association (OR = 7.00) increased risk, while preventive school policies (OR = 0.52) and high religiosity (OR = 0.36) reduced risk. Interaction effects between risk and protective factors were not significant, indicating that each factor operated consistently across respondent categories. These findings align with Problem Behavior Theory and highlight the protective roles of religiosity and school policies. The study concludes that online gambling exposure is shaped strongly by digital and social environments, whereas religious values and institutional policies act as safeguards. The implications include theoretical contributions to PGSI adaptation in Indonesia and practical recommendations for policymakers and educators to strengthen preventive interventions, enforce policies, and promote religious values